2022
DOI: 10.3171/2021.5.jns21772
|View full text |Cite
|
Sign up to set email alerts
|

The neurosurgical management of sinonasal malignancies involving the anterior skull base: a 28-year experience at The MD Anderson Cancer Center

Abstract: OBJECTIVE Sinonasal malignancies that extend to the anterior skull base frequently require neurosurgical intervention. The development of techniques for craniofacial resection revolutionized the management of these neoplasms, but modern and long-term data are lacking, particularly those related to the incorporation of endoscopic techniques and novel adjuvant chemotherapeutics into management schema. The present study was performed to better define the utility of surgical management and to determine factors rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Overall survival was 50% at a mean follow-up op 49 months. These results are in line with reports in the literature 7,8,16,17,20,21 . The most important predictor of survival is achieving gross total resection, while preserving quality of life 22 .…”
Section: Progression Free and Overall Survivalsupporting
confidence: 93%
“…Overall survival was 50% at a mean follow-up op 49 months. These results are in line with reports in the literature 7,8,16,17,20,21 . The most important predictor of survival is achieving gross total resection, while preserving quality of life 22 .…”
Section: Progression Free and Overall Survivalsupporting
confidence: 93%
“…Indeed, in a large institutional series that included 225 patients who were treated surgically for SNC over a 28-year period, found that the 5-year PFS rate for SNC was 52% and the 5-year OS rate was 65%. 10 Previous studies have demonstrated the poor prognosis associated with recurrent disease, especially when associated with skull base involvement. 13 The goals of this study were to determine whether skull base resection impacts the outcomes of well-selected patients with RSNC despite first-line therapy failure and to identify ad- ditional factors to be considered in the overall treatmentplanning process.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, endoscopic resection in a piecemeal fashion has been found to provide similar oncological control when compared with open en bloc resections. 10 Orbital involvement poses a particular challenge for patients with RSNC. Previous studies have shown that orbital invasion was associated with increased risk of death in patients with RSNC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations